Processes and practices of online „alternative‟ television programs in Zimbabwe: The case of Ruvheneko Live and #ThisFlag Thursday. - Khombo, Kennedy (Midlands State University, 2020)
The study explores the production and distribution processes and practices of online „alternative‟ television programs in Zimbabwe using the case of two internet based television programs namely Ruvheneko Live and #ThisFlag Thursday owned by Ruvheneko Parirenyatwa and Fadzayi Mahere respectively. The study also sought to unearth how online television programs in Zimbabwe such as the ones mentioned above make money and the effect of that on their programing. The study employed four distinct data collection methods namely online archival search, netnography, non-participant observation and in-depth interviews to gather data while thematic and interview analyses were used in the presentation and discussion of the findings. In the main, this study acknowledges the significances of the internet in creating alternative spaces for communication. However, it sharply disagrees with Dean‟s (2003) position that the advent of new platforms of communication such as the internet had revived the Habermasian concept of the public sphere characterized by free entry, free exit as well as freedom of opinion and expression as it unearthed various production and distribution processes and practices of the aforementioned online television programs that contradicts the key tenets of a true public sphere. In light of the findings of this study, the researcher recommends that online television programs in Zimbabwe should endeavor to be more inclusive of ordinary citizens in terms of their production and distribution processes and practices and avoid being driven by commercial, political or any exogenous interests thus keeping the true spirit and grain of the alternative nature of internet based communication spaces alive.